2012
DOI: 10.1080/17429145.2011.573151
|View full text |Cite
|
Sign up to set email alerts
|

Sequences and transcriptional analysis ofCoffea arabicavar. Caturra andCoffea libericaplant responses to coffee berry borerHypothenemus hampei(Coleoptera: Curculionidae: Scolytinae) attack

Abstract: The coffee berry borer (CBB) is the most prevalent pest of coffee plantations. Within the Coffea genus, C. arabica is susceptible to CBB and C. liberica shows a lower susceptibility. Two EST libraries were constructed from the total RNA of C. arabica and C. liberica fruits artificially infested with CBBs for 24 h. Using 6000 clones sequenced per library, a unigene database was generated, obtaining 3634 singletons and 1454 contigs. For each contig, the proportion of sequences present in both species was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 106 publications
2
5
0
1
Order By: Relevance
“…However, differential expression comparisons revealed that there were also changes dependent on the genotype, demonstrating that the response to the coffee berry borer infestation is genotype-dependent. 35 Further transcriptomics studies on arabica Colombia Supremo targeting genes from the phenylpropanoid pathway could validate the results presented in this study. Higher Levels of Sugar Alcohols and Organic Acids in Infested Robusta Suggesting Host Priming.…”
Section: ■ Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…However, differential expression comparisons revealed that there were also changes dependent on the genotype, demonstrating that the response to the coffee berry borer infestation is genotype-dependent. 35 Further transcriptomics studies on arabica Colombia Supremo targeting genes from the phenylpropanoid pathway could validate the results presented in this study. Higher Levels of Sugar Alcohols and Organic Acids in Infested Robusta Suggesting Host Priming.…”
Section: ■ Discussionsupporting
confidence: 73%
“…Both species showed overexpression of genes related to ethylene production and pathogen recognition when infested by the coffee berry borer. However, differential expression comparisons revealed that there were also changes dependent on the genotype, demonstrating that the response to the coffee berry borer infestation is genotype-dependent . Further transcriptomics studies on arabica Colombia Supremo targeting genes from the phenylpropanoid pathway could validate the results presented in this study.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…En condiciones de laboratorio se encontró una disminución entre 30% -40% de frutos infestados, menor cantidad de huevos ovipositados y menor sobrevivencia de la broca en frutos de Coffea liberica y tres introducciones de Coffea arabica del banco de germoplasma del Centro Nacional de Investigaciones de Café en Colombia (Romero & Cortina, 2004). Estudios de expresión génica en frutos infestados por broca encontraron una mayor expresión de proteínas involucradas en respuestas de defensas contra insectos en C. liberica (parcialmente resistente a broca) comparadas con C. arabica (susceptible a broca) (Idárraga et al, 2012). Estas dos especies de plantas también exhiben diferencias en la composición de volátiles emitidos por sus frutos (Cruz-Roblero & Malo, 2013).…”
Section: El Uso De Semioquímicos Como Estrategia Para Incrementar El Control Natural De Plagas De Caféunclassified